(untitled) (Avaliação: Revista da Avaliação da Educação Superior, 1997)
A avaliação institucional da Universidade Católica de Santos Martins, Maria Angélica Rodrigues; Vitório, Benalva da Silva; Coutinho, Cileda Queiroz e Silva; Pescuma, Derna